Peningkatan Pertumbuhan Bibit Kopi Arabica (Coffea arabica) terhadap Lama Perendaman Ekstrak Bawang Merah dan Perbandingan Beberapa Media Tanam - Refnizuida Refnizuida; Zamriyetti Zamriyetti; Linda Yusnita Siagian; Rohan Syahrizal Tambunan (UNIVERSITAS LABUHANBATU, 2022)
Coffee is one of the most important commodities in the world and ranks second after crude palm oil (CPO). One of the efforts that can be done to increase coffee production is to improve the quality of seeds. There are many obstacles in this effort because coffee needs to use several ways to speed up germination. One of the characteristics of coffee that makes it difficult to germinate is that the seeds are slimy and hard, this can be overcome by using onion extract. This study used a Randomized Block Design (RAK) with 2 factors and 2 blocks to obtain 32 research plots. Factor I. . The soaking time of the shallot extract (B) consists of 4 levels, namely: B0 : 0 without soaking, B1 : 3 hours, B2: 6 hours, B3 :9 hours. Factor II. Comparison of planting media with the symbol (K) which consists of 4 levels, namely: K0: topsoil, K1: compost, K2: compost + cow dung fertilizer (1:1), K3: compost + cow dung + husk charcoal. (1:1: 1). The research procedure consisted of Making Shallot Extract, Making Coffee Skin Compost, Making Cow Manure Organic Fertilizer, Analysis of Coffee Skin Compost, Analysis of Cow Manure Organic Fertilizer, Selection of Coffee Seeds, Stages of Seedling, Duration of Soaking Red Onion Extract, Stage of Sowing Coffee Beans, Determination of Sample Plants, Maintenance. Keywords : Coffee, Extract, Onion, Compost